Climate change-induced amplification of extreme temperatures in large lakes - Hazem U. Abdelhady; Ayumi Fujisaki-Manome; David Cannon; Andrew Gronewold; Jia Wang (Communications Earth & Environment)
Abstract Lake surface temperature extremes have shifted over recent decades, leading to significant ecological and economic impacts. Here, we employed a hydrodynamic-ice model, driven by climate data, to reconstruct over 80 years of lake surface temperature data across the world’s largest freshwater bodies. We analyzed lake surface temperature extremes by examining changes in the 10th and 90th percentiles of the detrended lake surface temperature distribution, alongside heatwaves and cold-spells. Our findings reveal a 20–60% increase in the 10 and 90 percentiles detrended lake surface temperature in the last 50 years relative to the first 30 years. Heatwave and cold-spell intensities, measured via annual degree days, showed strong coherence with the Arctic Oscillation (period: 2.5 years), Southern Oscillation Index (4 years), and Pacific Decadal Oscillation (6.5 years), indicating significant links between lake surface temperature extremes and both interannual and decadal climate teleconnections. Notably, heatwave and cold-spell intensities for all lakes surged by over 100% after 1996 or 1976, aligning with the strongest El-Niño and a major shift in the Pacific Decadal Oscillation, respectively, marking potential regional climate tipping points. This emphasizes the long-lasting impacts of climate change on large lake thermodynamics, which cascade through larger ecological and regional climate systems.